Biocrust diazotrophs and bacteria rather than fungi are sensitive to chronic low N deposition - Xiaoying Rong; Xiaobing Zhou; Xiangzhen Li; Minjie Yao; Yongxing Lu; Peng Xu; Benfeng Yin; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Environmental Microbiology, 2022)
Anthropogenic long‐term nitrogen (N) deposition may dramatically impact biocrusts due to the overarching N limitation of soil biota in deserts. Even low levels of N may reach a critical loading threshold altering biocrust constituents and function. To identify the impact of chronic and continuous low levels of N deposition on biocrusts, we created a realistic gradient mirroring anthropogenic N addition rate (2:1 NH 4 + : NO 3 − rates: 0.3, 0.5, 1.0, 1.5, 3 g N m −2 yr −1 ) and measured the response of bacteria and fungi within cyanobacterial‐dominated biocrusts over 8 years in a temperate desert, the Gurbantunggut Desert, China. We found that once N deposition reached 1.5 g N m −2 yr −1 biocrust bacterial communities, including diazotrophs, were altered while no such tipping point existed for fungi. Above the threshold, bacterial richness was enhanced, the relative abundance of Chloroflexi, FBP and Gemmatimonadetes was elevated, and diazotrophs shifted from being dominated by Nostocaceae and Scytonemataceae (Cyanobacteria) to free‐living Bradyrhizobiaceae (Alphaproteobacteria). Alternatively, the relative recovery of a few fungal species within the Lecanorales, Pleosporales and Verrucariales became either enriched or diminished due to N deposition. The chronic addition of N resulted in a dense and interconnected bacterial co‐occurrence network that accentuated a functional shift from networks dominated by phototrophic species within the Nostocaceae, Xenococcaceae, Phormidiaceae and Scytonemataceae (Cyanobacteria) to ammonia‐oxidizing species within the Nitrosomonadaceae (Betaproteobacteria) and nitrifying bacteria [i.e. Nitrospiraceae (Nitrospirae)]. Based on structural equation models, the effects of N additions on biocrust constituents were imposed through indirect effects on pH, soil electrical conductivity and ammonium concentrations. In summary, biocrust constituents are generally insensitive to chronic low levels of N depositions until rates reach above 1.5 g N m −2 yr −1 with diazotrophs being the most sensitive biocrust constituents followed by bacteria and finally fungi. Ultimately once the threshold is reached N deposition favours biocrust constituents utilizing inorganic N and other C sources over relying on phototrophic and/or N‐fixing cyanobacteria for C and N.

A new atypical short‐chain dehydrogenase is required for interfungal combat and conidiation in Trichoderma guizhouense - Hong Zhu; Jian Zhang; Qi Gao; Guan Pang; Tingting Sun; Rong Li; Zhenzhong Yu; Qirong Shen (Environmental Microbiology, 2021)
Summary Hypocrealean Trichoderma are the most extensively studied facultative mycoparasites against phytopathogenic fungi. Aerial hyphae of Trichoderma guizhouense can rapidly proliferate over Fusarium oxysporum hyphae, cause sporadic cell death and arrest the growth of the host. The results of the present study demonstrated that a unique short‐chain dehydrogenase/reductase (SDR), designated as TgSDR1, was expressed at a high level in T . guizhouense challenged by the hosts. Similar to other SDRs family members, the TgSDR1 protein contains a cofactor‐binding motif and a catalytic site. The subcellular localization assay revealed that the TgSDR1::GFP fusion protein translocated to lipid droplets in mycelia and conidia. The data obtained using reverse genetic approach indicated that TgSDR1 is associated with antifungal ability, plays an important role in providing reducing equivalents in the form of NADPH and regulates the amino sugar and nucleotide sugar metabolism in T . guizhouense upon encountering a host. Moreover, the TgSDR1 deletion mutant was defective in conidiation. Thus, TgSDR1 functions as a key metabolic enzyme in T . guizhouense to regulate mycotrophic interactions, defence against other fungi, such as F . oxysporum , and conidiation.

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Expression of HopAI interferes with MAP kinase signalling in Magnaporthe oryzae - Xue Zhang; Wende Liu; Yang Li; Guotian Li; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary The Pmk1 and Mps1 MAP kinases are essential for appressorium formation and plant infection in Magnaporthe oryzae . However, their exact roles during invasive growth are not clear because pmk1 and mps1 mutants are defective in penetration. To further characterize their functions after penetration, in this study we expressed the Pseudomonas syringae effector HopAI known to inactivate plant MAP kinases in M. oryzae . Constitutive expression of HopAI with the RP27 or TrpC promoter resulted in defects in hyphal growth, conidiation, appressorium penetration and pathogenicity, which is similar to the phenotype of the mps1 mutant. HopAI interacted strongly with Mps1 in vivo and expression of dominant active MKK2 partially suppressed the defects of P RP27 ‐HopAI transformants, which were significantly reduced in Mps1 phosphorylation. When the infection‐specific MIR1 ( Magnaporthe ‐infection‐related gene‐1) promoter was used to express HopAI, P MIR1 ‐HopAI transformants were defective in the spreading of invasive hyphae and elicited strong defense responses in penetrated plant cells. Expression of HopAI in Fusarium graminearum also mainly affected the activation of Mgv1, an Mps1 orthologue. Taken together, our results showed that Mps1 is the major intracellular target of HopAI when it is overexpressed, and MAP kinase signalling is important for cell‐to‐cell movement of invasive hyphae in M. oryzae .

Temperature‐mediated local adaptation alters the symbiotic function in arbuscular mycorrhiza - Rong Yang; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Environmental Microbiology, 2017)
Summary Variation in the symbiotic function of arbuscular mycorrhizal fungi (AM fungi) has been demonstrated among distinct biotic and abiotic interactions. However, there is little knowledge on how local temperature conditions influence the functional divergence of AM symbionts in alpine ecosystems. Here, we conduct a reciprocal inoculation experiment to explore the three‐way interactions among plants, AM fungal inoculum and temperature at sites of contrasting elevation. Evidence of local adaptation of plant growth was found only under low temperature conditions, with no consistent local versus foreign effect found in AM fungal performance. The origin of either the plant or the inoculum relative to the temperature was important in explaining symbiotic function. Specifically, when inoculum and temperature were sympatric but allopatric to the plant, poor adaptation by the plant to the novel environment was clearly found under both temperature conditions. Further analysis found that the symbiotic function was inversely related to fungal diversity under high temperature conditions. These results suggest that local adaptation represents a powerful factor in the establishment of novel combinations of plant, inoculum and temperature, and confirms the importance of taking into account both biotic and abiotic interactions in the prediction of the response of symbionts to global environmental change.

MST50 is involved in multiple MAP kinase signaling pathways in Magnaporthe oryzae - Guotian Li; Xue Zhang; Huan Tian; Yoon‐E Choi; W. Andy Tao; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary Appressorium formation plays a critical role in Magnaporthe oryzae . Mst50 is an adapter protein of the Mst11‐Mst7‐Pmk1 cascade that is essential for appressorium formation. To further characterize its functions, affinity purification was used to identify Mst50‐interacting proteins (MIPs) in this study. Two of the MIPs are Mst11 and Mst7 that are known to interact with Mst50 for Pmk1 activation. Surprisingly, two other MIPs are Mck1 and Mkk2 that are the upstream kinases of the Mps1 pathway. Domain deletion analysis showed that the sterile alpha‐motif of Mst50 but not the Ras‐association domain was important for its interaction with Mck1 and responses to cell wall and oxidative stresses. The mst50 mutant was reduced in Mps1 activation under stress conditions. MIP11 encodes a RACK1 protein that also interacted with Mck1. Deletion of MIP11 resulted in defects in cell wall integrity, Mps1 phosphorylation and plant infection. Furthermore, Mst50 interacted with histidine kinase Hik1, and the mst50 mutant was reduced in Osm1 phosphorylation. These results indicated that Mst50 is involved in all three MAPK pathways in M. oryzae although its functions differ in each pathway. Several MIPs are conserved hypothetical proteins and may be involved in responses to various signals and crosstalk among signaling pathways.

Thioredoxins are involved in the activation of the PMK1 MAP kinase pathway during appressorium penetration and invasive growth in Magnaporthe oryzae - Shijie Zhang; Cong Jiang; Qiang Zhang; Linlu Qi; Chaohui Li; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary In Magnaporthe oryzae , the Mst11‐Mst7‐Pmk1 MAP kinase pathway is essential for appressorium formation and invasive growth. To determine their roles in Pmk1 activation and plant infection, we characterized the two thioredoxin genes, TRX1 and TRX2 , in M. oryzae . Whereas the Δ trx1 mutants had no detectable phenotypes, deletion of TRX2 caused pleiotropic defects in growth, conidiation, light sensing, responses to stresses and plant infection progresses. The Δ trx1 Δ trx2 double mutant had more severe defects than the Δ trx2 mutant and was non‐pathogenic in infection assays. The Δ trx2 and Δ trx1 Δ trx2 mutant rarely formed appressoria on hyphal tips and were defective in invasive growth after penetration. Pmk1 phosphorylation was barely detectable in the Δ trx2 and Δ trx1 Δ trx2 mutants. Deletion of TRX2 affected proper folding or intra‐/inter‐molecular interaction of Mst7 and expression of the dominant active MST7 allele partially rescued the defects of the Δ trx1 Δ trx2 mutant. Furthermore, Cys305 is important for Mst7 function and Trx2 directly interacts with Mst7 in co‐IP assays. Our data indicated that thioredoxins play important roles in intra‐cellular ROS signalling and pathogenesis in M. oryzae . As the predominant thioredoxin gene, TRX2 may regulate the activation of Pmk1 MAPK via its effects on Mst7.

Activation of the signalling mucin MoM sb2 and its functional relationship with C bp1 in M agnaporthe oryzae - Guanghui Wang; Guotian Li; Shijie Zhang; Cong Jiang; Jun Qin; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Various surface signals are recognized by M agnaporthe oryzae to activate the P mk1 MAP kinase that is essential for appressorium formation and invasive growth. One of upstream sensors of the P mk1 pathway is the MoM sb2 signalling mucin. However, the activation of MoM sb2 and its relationship with other sensors is not clear. In this study, we showed that the cleavage and transmembrane domains are essential for MoM sb2 functions. Cleavage of MoM sb2 was further confirmed by western blot analysis, and five putative cleavage sites were functionally characterized. Expression of the extracellular region alone partially rescued the defects of M omsb2 in appressorium formation and virulence. The cytoplasmic region of MoM sb2, although dispensable for appressorium formation, was more important for penetration and invasive growth. Interestingly, the M omsb2 cbp1 double mutant deleted of both mucin genes was blocked in P mk1 activation. It failed to form appressoria on artificial surfaces and was non‐pathogenic. In addition, we showed that MoM sb2 interacts with R as2 but not with MoC dc42 in co‐immunoprecipitation assays. Overall, results from this study indicated that the extracellular and cytoplasmic regions of MoM sb2 have distinct functions in appressorium formation, penetration and invasive growth, and MoM sb2 has overlapping functions with C bp1 in recognizing environmental signals for P mk1 activation.

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.